Theoretical and Empirical Analysis of Relational Marketing in Educational Institutions: A Literature Review - Kurnia Alkafi; Sarmain Sarmain; Anis Zohriah; Abdul Muin; Muhammad Afif (Al-Qalam Institue, 2025)
The rapid digital transformation in the post-pandemic era has significantly reshaped the educational landscape, making it essential for institutions to adopt modern marketing strategies to remain competitive. This research explores the role of relational marketing in enhancing institutional reputation, student loyalty, and retention, particularly in the context of Indonesian educational institutions. The study aims to understand how relational marketing techniques, including CRM systems, digital branding, and social media engagement, can be effectively implemented to foster long-term relationships with students, parents, and alumni. A Systematic Literature Review (SLR) was employed to synthesize relevant studies from 2021 to 2025, focusing on relational marketing in education. The findings reveal that relational marketing strategies significantly contribute to student satisfaction and retention, with technology playing a pivotal role in personalizing services and communication. However, challenges such as limited resources and technological adoption remain. The study concludes that overcoming these challenges and integrating relational marketing strategies effectively can ensure the long-term sustainability and competitiveness of educational institutions in a digital era.